Pengaruh Kombinasi Ekstrak Daun Keji Beling (Strobilanthes crispus) dan Daun Singkil (Premna corymbose Rottl. et Willd) terhadap Intensitas Serangan Serangga Hama pada Tanaman Terung Hijau (Solanum melongena L.) - Miranda Miranda; Sonja Verra Tinneke Lumowa; Ruqoyyah Nasution; Herliani Herliani (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effect of the combination of keji beling leaf extract (Strobilanthes crispus) and singkil leaf (Premna corymbose Rottl. et Willd) on the intensity of insect pest attacks on green eggplant (Solanum melongena L.). The study used a Randomized Block Design (RBD) with five treatments, namely control (water) and a combination of extracts at concentrations of 25%, 40%, 55%, and 70%, each repeated five times. The extract was made by maceration method using water as a solvent and additional natural adhesive (3 g detergent). Application was carried out twice per week, and the intensity of insect pest attacks was observed on days 11, 25, 39, and 53 DAP. Data were analyzed using ANOVA and the Least Significant Difference (LSD) test at a significance level of 1%. The results showed that the combination of extracts had a very significant effect on the intensity of insect pest attacks (F count > F table). The 70% concentration gave the lowest attack intensity, which was around 15%. This combination of extracts has the potential to be an environmentally friendly botanical pesticide for controlling insect pests on green eggplant plants.